PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING(PBL) UNTUK MENINGKATKAN HASIL BELAJAR DI SD NEGERI RANCABOGO II - Ina Marlina; Rayi Siti Fitriani; Citra Octrapramudia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to analyze the effect of Project-Based Learning (PBL) on students' learning outcomes while examining its implementation in supporting the development of 21st-century skills. The study employed a quantitative approach using a pre-experimental One Group Pretest-Posttest Design. The participants consisted of 20 fourth-grade students at SD Negeri Rancabogo II, Subang Regency, Indonesia. Data were collected through pretest and posttest instruments consisting of ten essay questions. The data were analyzed descriptively and inferentially using the Shapiro-Wilk normality test and the Wilcoxon Signed Rank Test. The results indicated that the mean score increased slightly from 9.45 on the pretest to 9.60 on the posttest. Of the participants, 25% showed improved scores, 55% maintained the same scores, and 20% experienced a slight decline. Although a modest increase in the average score was observed, the N-Gain value of 0.0198 (1.98%) indicated a very low level of effectiveness. Classroom observations further revealed that limited reading ability among several students and suboptimal classroom management influenced the learning outcomes. Therefore, the implementation of Project-Based Learning did not produce a substantial improvement in students' learning outcomes within the context of this study, although it demonstrated potential for fostering more active and student-centered learning. Strengthening students' basic literacy skills, improving classroom management, and implementing PBL more consistently are recommended to enhance instructional effectiveness.